The regulatory aftermath of the global financial crisis / Eilís Ferran [and others] ; with a foreword by Ethiopis Tafara. - Ferran, Eilís (International corporate law and financial market regulation., 2012)
The EU and the US responded to the global financial crisis by changing the rules for the functioning of financial services and markets and by establishing new oversight bodies. With the US Dodd-Frank Act and numerous EU regulations and directives now in place, this book provides a timely and thoughtful explanation of the key elements of the new regimes in both regions, of the political processes which shaped their content and of their practical impact. Insights from areas such as economics, political science and financial history elucidate the significance of the reforms. Australia's resilience during the financial crisis, which contrasted sharply with the severe problems that were experienced in the EU and the US, is also examined. The comparison between the performances of these major economies in a period of such extreme stress tells us much about the complex regulatory and economic ecosystems of which financial markets are a part.